Ameliorative Response of Humic Acid and Plant Growth Promoting Rhizobacteria on Soil Microorganism Population in the Northern Region of India - Bhatt, Pooja; Singh, V.K; Kumar, Sanjeev; Chaudhary, Parul (Ecological Questions, 2025)
Soil microorganisms play a vital role in improving soil fertility. The addition of organic amendments increases the microbial population in the soil. The present study aimed to investigate and compare the impact of organic amendments (HA-Humic acid and PGPR -Plant growth-promoting bacteria) and recommended dose of fertilizer (RDF) solely and in combination on the soil’s microbial population (fungi, actinomycetes, and bacteria). The two years of study were investigated at GB Pant University of Agriculture and Technology during winter. The experiment was designed using a randomized block design (RBD), and it consisted of ten treatments and three replications. HA (2.5 kg/ha- soil application, 20 g/kg-seed treatment), PGPR (20 g/kg seeds), and RDF (150 kg/ha) are all used individually or in combination. The result shows that the T10 (RDF + HA-2.5 kg/ha (soil application) + PGPR -20 g/kg seed (seed treatment) significantly increases the population of fungi, bacteria, and actinomycetes 42.54, 35.57, & 41.87% and 21.14, 41.11 & 49.38% over T5 (RDF) at 70 days after sowing in the first and second year, respectively. Also, soil application of HA was found to be more effective than seed treatment in increasing microbial population. The study concluded that applying HA and PGPR enhances the biological properties of soil and can minimize the fertilizer dose, which can be a better approach for sustainable agriculture.